Blockchain-Based Railway Ticketing: Enhancing Security and Efficiency with QR Codes and Smart Contract - Farhan, Maruf; Nur, Abdullah Hafez; Sulaiman, Rejwan Bin; Butt, Usman; Zaman, Snigdha (2025 4th International Conference on Computing and Information Technology (ICCIT), 2025)
In light of the increasing prevalence of railway ticketing fraud, it is imperative to implement advanced technological solutions to guarantee the integrity and security of ticket transactions. The blockchain technology's decentralized, transparent, and immutable record-keeping method has the potential to address these problems. The utilization of blockchain technology in railway ticketing systems is being analyzed with the aim of enhancing the detection and prevention of fraudulent activities. Smart contracts ensure the security of each transaction by enabling quick verification and minimizing issues such as ticket duplication, illegal modifications, and counterfeit tickets. A blockchain system guarantees the genuineness and validity of tickets for passengers, railway personnel, and ticketing agencies. The report also explores the incorporation of blockchain technology into rail ticketing systems as an adaptable and robust remedy for fraud. Resolving challenges related to the deployment of scalability, data protection, and regulatory compliance. The study conducts a simulation and analysis of the blockchain-based system, revealing a substantial reduction in fraudulent activities. The findings of our study demonstrate that the system effectively eradicates ticket fraud, enhances operational efficiency, and is financially feasible with an adoption cost of 3.54. This enhances the efficiency and reliability of train ticketing.